Increasing Student’s Character Values by Utilizing Combination of Team Accelerated Instruction (TAI) and Numbered Heads Together (NHT) - Nuryana, Ita; Widhiastuti, Ratieh; Murniawaty, Indri (Dinamika Pendidikan, 2016)
This research aims to obtain empirical evidence of the effectiveness of combining Team Accelerated Instruction (TAI) and Numbered Heads Together (NHT) learning strategies in teaching Investments to improve students’ discipline, creativity, diligence, and participation. Population was students who enrolled in Intermediate Financial Accounting 2 course in Economics Education Department; Economics Faculty of Universitas Negeri Semarang The sample of the research consists of 48 students. Data were collected by using observations, interviews, and documentation. The stages of the research include planning, implementation, monitoring and evaluation, analysis, and reflection. Findings show that the combination of TAI and NHT does not improve students’ learning outcomes even thought it manages to increase students’ pre-test score in learning Investments as well as their participation in classroom.